Fenugreek residue as nutraceutical and antibacterial agent in broiler ration - PURUSHOTHAMAN, M R; CHANDRASEKARAN, D; JANANI, S R (The Indian Journal of Animal Sciences, 2014)
A study was conducted in broiler chicken for 6 weeks to find out the efficacy of fenugreek residue (FR) as an additive in poultry rations and to evaluate the nutraceutical property of FR as a replacement of antibiotic (AB) in broiler rations. Day-old broiler chicks (216) were divided into 9 treatment groups, each treatment group had 3 replicates with 8 birds in each replicate. The treatments were 0, 0.5, 1.0, 1.5 and 2.0 % FR with and without antibiotic (500 g of 10% oxytetracycline/tonne). At the end of 6 weeks (0 – 42 day), the body weight gain was comparable with the control, whereas significantly higher feed intake and poor FCR was found in 1.0% and 1.5% FR without AB group than the control. Slaughter studies with 6 birds/treatment group were conducted at the end of the experiment revealed that dressing %, giblet and abdominal fat (g/kg body weight) did not vary among the groups. The blood glucose was not influenced and muscle cholesterol levels reduced in all treatment groups than the control. The intestinal bacterial Escherichia coli and Clostridium spp. count was found to be reduced in FR without AB, however FR with AB fed birds have intestinal Clostridium content comparable (0.5 and 2.0% FR) or higher (1.0 and 1.5% FR) than the control. Inclusion of FR with AB provided better returns over that of control. Supplementation of FR up to 2% with or without AB (except 1.5% FR without AB) in feed improved the performance of birds and reduced the feed cost per unit gain.